2020
DOI: 10.3390/ijerph17186699
|View full text |Cite
|
Sign up to set email alerts
|

COD19 and COD20: An Italian Experience of Active Home Surveillance in COVID-19 Patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic found Italy unprepared to cope with the large concentrated numbers of patients infected with coronavirus disease 2019 (COVID-19) who often required hospital admission and in many cases intensive care. This pandemic very quickly overwhelmed the Italian Healthcare System. This paper describes the Active Home Surveillance System (Operations Center for Discharged Patients; COD19) and the Home Hospital Care System (COD20) and presents the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…In telehealth solutions with treatment purpose, the aim was to provide necessary recommendations to symptomatic patients to reduce their symptoms. Most of the patients who received this type of services were confirmed cases (13,36,39,44,45,50,52,57,58,60,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73).…”
Section: Function Typementioning
confidence: 99%
“…In telehealth solutions with treatment purpose, the aim was to provide necessary recommendations to symptomatic patients to reduce their symptoms. Most of the patients who received this type of services were confirmed cases (13,36,39,44,45,50,52,57,58,60,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73).…”
Section: Function Typementioning
confidence: 99%
“…The terms telehealth and telemedicine are usually employed interchangeably, but telehealth has developed to encapsulate a wider range of digital health care activities and services [25]. In fact, where telemedicine is specifically referred to as the practice of medicine by remote means, telehealth is an inclusive expression that includes all health care and health system components and activities that are conducted through telecommunications technology [26][27][28][29].…”
Section: Telehealth and The Covid-19 Eramentioning
confidence: 99%
“…Zuccotti et al recently reported an Italian project about the implementation of active domiciliary monitoring (COD19) and a homecare hospital system (COD20) in COVID-19 patients, supported by the certified Amazon Web Services Serverless platform [25]. This monitoring system provides continuous assessment of critical medical status, detection of socially and clinically relevant issues, and the supply of necessary clinical services as a telemedicine service.…”
Section: Telehealth and The Covid-19 Eramentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the Operations Center for Discharged Patients (Centrale Operativa Dimessi, COD19) was created as an active home surveillance system. 6 With the emerging evidence of long-term sequelae of COVID-19, COD19 started a oneyear follow-up of patients originally monitored during the first Italian phase of the pandemic. The purpose of this study is to report the clinical consequences in the population affected by COVID-19, both inpatients and outpatients, 12 months after the recovery from the acute illness.…”
Section: Introductionmentioning
confidence: 99%